Pengaruh Islam dalam Pembentukan Kerajaan-Kerajaan di Sumatera dan Pantai Utara Jawa - Purnamasari, Ika; Simaremare, Elsa Manora; Dhalimunte, Sadina Yanti; Marpaung, Adrian; Sihotang, Marnita; Nazwa, M. Dirham (Medan Resource Center, 2024)
This article reviews the development of Islamic kingdoms in Sumatera and the North Coast of Java from the pre-colonial to early colonial period. In Sumatera, kingdoms such as Samudera Pasai, Aceh Darussalam, and Palembang Darussalam played an important role in the spread of Islam through trade, education, and diplomacy. Samudera Pasai became the first center of trade and the spread of Islam in Indonesia, while Aceh Darussalam reached its peak of glory in the 16th and 17th centuries with its military strength and influence in Southeast Asia. Palembang Darussalam became an important trade center in southern Sumatera. On the North Coast of Java, kingdoms such as Demak, Cirebon, and Banten played a significant role in the spread of Islam. Demak, founded by Raden Patah, is known as the first Islamic kingdom in Java and played a role in overthrowing Majapahit. Cirebon developed as a religious and cultural center under Sunan Gunung Jati, while Banten became the dominant maritime and trade power in the Sunda Strait. This study uses a historical approach by analyzing chronicles, hikayat, and travel notes. The results show that the development of these Islamic kingdoms was influenced by political, economic, social, and cultural factors, including the influence of ulama, international trade, and interactions with foreign powers such as the Portuguese and the Dutch. In conclusion, the Islamic kingdoms in Sumatera and the North Coast of Java played a key role in the spread of Islam in the archipelago and in the political, economic, and cultural development of the region, providing a significant historical legacy for the development of Islam in Indonesia.